2020
DOI: 10.1016/j.heliyon.2020.e05857
|View full text |Cite
|
Sign up to set email alerts
|

Biological decolorization of Amaranth dye with Trametes polyzona in an airlift reactor under three airflow regimes

Abstract: In the present work, a strain of the basidiomycete fungus Trametes polyzona was used to decolorize the Amaranth dye. The decolorization was carried out in an Airlift reactor with three flow regimes: 1, 2, and 3 vvm. The results showed that the decolorization was a function of the flow regime. The decolorization times for the regimes of 1, 2, and 3 vvm were 30, 25, and 19 days, respectively. The COD (Chemical Oxygen Demand) decreased from 1600 to 72 mg COD/L. The enzymatic activity kinetics of laccase (Lcc), li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…After being treated with the addition of T. yunnanense isolate, the pH value was decreased in the range of 7.14. In this study, high levels of BOD (21,881.34 mg L -1 ) and COD (50,909.09 mg L -1 ) in batik waste indicated high toxicity, so it is very dangerous to environment and health human (Pérez-Cadena et al 2020). The decrease in BOD and COD levels by T. yunnanense can result from the removal of organic loads from batik waste that reduce toxicity.…”
Section: Decolorization and Physico-chemical Analysis Of Batik Wastementioning
confidence: 66%
“…After being treated with the addition of T. yunnanense isolate, the pH value was decreased in the range of 7.14. In this study, high levels of BOD (21,881.34 mg L -1 ) and COD (50,909.09 mg L -1 ) in batik waste indicated high toxicity, so it is very dangerous to environment and health human (Pérez-Cadena et al 2020). The decrease in BOD and COD levels by T. yunnanense can result from the removal of organic loads from batik waste that reduce toxicity.…”
Section: Decolorization and Physico-chemical Analysis Of Batik Wastementioning
confidence: 66%
“…Among them, agitation can affect fungi by supplying oxygen and nutrients, and also, it can affect the mycelial network by damaging the fungi. Perez-Cadena et al (2020) observed that decolorization efficiency of azo dyes by Trametes polyzona increased by increased agitation rate. They argued that with the increase of aeration, the biomass increases, and this positively affects the electron transfer that results in increased enzymatic activity (Perez-Cadena et al, 2020;Hadibarata and Kristanti., 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Perez-Cadena et al (2020) observed that decolorization efficiency of azo dyes by Trametes polyzona increased by increased agitation rate. They argued that with the increase of aeration, the biomass increases, and this positively affects the electron transfer that results in increased enzymatic activity (Perez-Cadena et al, 2020;Hadibarata and Kristanti., 2012). In our case, because there is no nutrient in the solution, it can be anticipated that the increase in the amount of oxygen with agitation and the fragmentation of the mycelium played a positive role on the adsorption rate.…”
Section: Discussionmentioning
confidence: 94%
“…Pakshirajan & Kheria (2012) observed an agreement of 64% decolorization efficiency with 73% COD reduction of diluted textile wastewater by immobilized P. chrysosporium within 2 days [23]. Moreover, other research showed similar relation with longer treatment days between 12−70 days in the optimum treatment conditions and/or by using synthetic dyes [37,38]. A recent study by Dalecka et al…”
Section: Monitoring Of Ph and Cod Removalmentioning
confidence: 85%